Search and seizure, production and preservation of electronic evidence - Nieman, Annamart (North-West University, 2006)
Criminals are becoming increasingly involved in computing activity and connectivity, but practitioners in the criminal justice field do not seem to be keeping pace with crime in a computing context. Being comfortable with the technology that underpins the Information Age is a non-negotiable skill for those who have to unravel and bring twenty-first century crimes to book. Chapter two of this study therefore sought to serve two purposes. The first aim was to acquaint the reader with the exceedingly complex technologies involved in computers and networks. The second aim was to clarify the technical context and terminology typical of the collection of electronic evidence. South Africa signed the Cybercrime Convention in November 2001. At present, the Cybercrime Convention is the only existing internationally accepted benchmark, inter alia, for the procedural powers aimed at the collection of electronic evidence. The main objective of this study was to consider whether the South African search and seizure, production and preservation devices need to be augmented and/or aligned so as to be on par with the devices proposed in the Cybercrime Convention. This objective was served in two ways. Firstly, an exposition of the requirements, scope, conditions and safeguards of the domestic and transborder search and seizure, production and preservation mechanisms proposed by the Cybercrime Convention was provided in chapter three of this study. Secondly, an exposition of the domestic and transborder international search and seizure, production and preservation devices available in the current South African legislative framework was given in chapter four of this study. A comparative analysis was done between the South African catalogue of criminal procedural search and seizure, production and preservation devices compared to those set out in the Cybercrime Convention. Where any alignment or augmentation of the South African devices was found to be necessary, this study identified these intervention areas. The findings and recommendations based on this comparative analysis were set out in chapter seven of this study. In considering any alignments and/or augmentations required in respect of the South African domestic search and seizure, production and preservation mechanisms, the application of the equivalent mechanisms directed at electronic evidence used in the United States of America and England were investigated in chapters five and six respectively. The lessons learned were also referred to in chapter seven of this study.